Inadvertence and Moral Responsibility - Harry Frankfurt (Ideas y Valores, 2009)
Against the view of certain philosophers, such as Thomas Nagel, I defend the common sense belief that people are not responsible for what they do or bring about inadvertently. I consider what response we might reasonably expect from a person who inadvertently does or brings about some event or condition that is manifestly undesirable or bad; and I suggest that we might reasonably expect such a person not to feel guilty but, rather, to feel embarrassed by his or her inability to prevent or avoid that condition or event.